The Evaluation of the Performance and Economics of Solar Tracking System for Bifacial Solar Panel - Beangthit, Jirayu; Polvongsri, Sarawut (RMUTL Engineering Journal, 2024)
This research assessed the performance and economic viability of a bifacial solar tracking system for a 430 Wp solar panel. The system was designed and tested using an iterative process to adjust the panel tilt angle based on specified conditions. The performance evaluation of the solar tracking system for the bifacial solar panel revealed a 2.31% error in the designed and installed systems. The tracked system achieved a maximum power output of 364.20 W with a power generation efficiency of 13.01%, compared to the non-tracked system that produced a maximum power of 360.42 W with an efficiency of 12.05%. The capacity of electric generation from the 1 MW two-side solar cell system was determined the established equations. From the result, the solar tracking system produced 1,758.78 MWh/year, higher than the without-tracking system with 1,579.41 MWh/year. In terms of economic viability, the solar tracking system provided a payback period of 7.01 years, longer than the without-tracking system with a payback period of 6.38 years. The net present values were 11,910,512.54 Baht and 14,692,713.81 Baht for the tracking and without-tracking systems, respectively, with internal rates of return of 10.80% and 12.80%, respectively.